THE EFFECT OF THE HISTORY LEARNING VIDEO-BASED PROJECT-BASED LEARNING MODEL IN INCREASING STUDENT LEARNING MOTIVATION IN HIGH SCHOOL - Fitriyah Fitriyah; Miftahuddin Miftahuddin; Rhoma Dwi Yuliantri; Nurhijrah Binti Zakaria (JETL (Journal of Education, Teaching and Learning), 2025)
The purpose of this study is to assess how high school students' motivation to learn can be increased by using the Project Based Learning (PjBL) learning paradigm, which is based on historical learning films. A quasi-experimental quantitative method is employed in the research process. Through student knowledge assessments, interviews, and observational methods, data was gathered. Using SPSS 25 software, t-and N-Gain tests were used to quantitatively analyze the data. Following the implementation of the learning model, the t-test yielded a significance value (2-tailed) of 0.000, which was less than 0.05, according to the data, showing a significant difference in the students' post-test scores. In addition, the N-Gain analysis showed an increase from the low category (0.22) in the pretest to the medium category (0.61) in the posttest, indicating the effectiveness of this learning model in increasing students' learning motivation. The study's conclusion is that the PjBL learning model, which is based on historical learning videos, significantly affects students' motivation to learn. This finding may be used as a guide to create future learning strategies that are even more successful.